Chair of Mathematical Logic and Theory of Algorithms - Semenov, A. L.; Babenko, M. A.; Belov, A. Ya; Vereshchagin, N. K.; Vishnikin, M. E.; Zolin, E. E.; Krupski, V. N.; Kuznetsov, S. L.; Lyubetsky, V. A.; Onoprienko, A. A.; Pentus, M. R.; Soprunov, S. F.; et al. (Moscow University mathematics bulletin, 2025)
The paper describes the history of the creation and activities of the Chair of Mathematical Logic and Theory of Algorithms at Lomonosov Moscow State University. A brief description of the areas of work and achievements of graduates of the chair and its fellows is given.